Goat and sheep products value chain analysis in Lebanon - Hosri C.; Tabet E.; Nehme M. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The small ruminant’s production in Lebanon is facing many difficulties related to the grazing potential, the feeding cost, the labor fees, the know-how and the marketing of the products. This value chain of small ruminants could not be saved from extinction, except if it is capable of holding its economic and social impact. The goat and sheep value chain analysis is the simple reasoning behind this study and it is absolutely necessary to protect these traditional products. The zootechnic and economic analysis of the milk and meat is conducted at all levels of the value chain starting by the input suppliers, the breeders, the products collectors, the products processors and products commercialization. The main breeds used are the local population of goats called “baladi” and the Awassi sheep. They are mainly raised in extensive systems with different levels of concentrate supplementations. The minor cases of intensive production raise mainly the imported breeds of goats (damasquine, saneen, alpine) and the Awassi sheep. Whereas in the north of Lebanon Mountains the goat meat is more usually consumed, in other areas sheep meat consumption is dominant. The dairy products are mainly processed at the artisanal level and the SME’s occupy a special market chain.The results of this study will help to get a better knowledge of the value chain weaknesses, and it will serve as a guide for the sector improvement.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)